2000
DOI: 10.1046/j.1460-2695.2000.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical note A study on stress, reflection and double shot peening to inrease compressive residual stress

Abstract: The technique of shot peening is commonly used to increase the fatigue limit of a steel. However, there are many practical difficulties in applying it to very high HV steel and complicated components. To overcome these problems, the authors proposed two new methods: stress double shot peening and stress reflection double shot peening. Both techniques were applied to quench and tempered steel (QT steel) and induction‐heated steel (IH steel). The main results were as follows: (a) by double shot peening, the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In general, increasing the hardness and the introduction of compressive residual stresses are effective methods for improving fatigue limits. While a hardness increase is known to increase the sensitivity of the material to defects, introducing compressive residual stresses by shot peening (SP) is widely used to improve the fatigue limits of vehicle parts (Suresh, 1991;Mitsubayashi et al, 1995;Ishigami et al, 2000;Webster et al, 2001;Guaglian et al, 2002;Lang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In general, increasing the hardness and the introduction of compressive residual stresses are effective methods for improving fatigue limits. While a hardness increase is known to increase the sensitivity of the material to defects, introducing compressive residual stresses by shot peening (SP) is widely used to improve the fatigue limits of vehicle parts (Suresh, 1991;Mitsubayashi et al, 1995;Ishigami et al, 2000;Webster et al, 2001;Guaglian et al, 2002;Lang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Residual stress ③ assumes that stress peening is performed as described in literature. 26,27 The stress range (Δσ w ) at the fatigue limit of a nonshot-peened smooth specimen (hereinafter, NonSP smooth specimen) was 840 MPa. The fatigue limit (Δσ s ) of the shot-peened smooth specimen (hereinafter, SP smooth specimen) was assumed to be 950 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmoudi et al studied the effect of initial compressive residual stress on subsequent compressive residual stress induced by shot peening and found that the initial residual stress was wiped out by shot peening up to the maximum compressive residual stress point. 14 Voorwald et al have investigated the effect of shot peening on rotating bending fatigue strength of chromium electroplated AISI 4340 steel for landing gear applications, and they found that the fatigue strength improved. 10 Takahashi et al investigated the effect of shot peening on the torsional fatigue limit in specimens containing artificial defects in highstrength steel specimens and found that the defect with specific dimensions could be rendered harmless by shot peening.…”
Section: Introductionmentioning
confidence: 99%
“…13 Ishigami et al have studied the influence of stress double shot peening and stress reflection double shot peening methods to quenched and tempered steel, and they found that the latter induced greater compressive residual stress at the outer surface of specimens. 14 Voorwald et al have investigated the effect of shot peening on rotating bending fatigue strength of chromium electroplated AISI 4340 steel for landing gear applications, and they found that the fatigue strength improved. They also showed that the peening process using ceramic shots resulted in lower scatter in rotating bending fatigue data than the steel shots.…”
Section: Introductionmentioning
confidence: 99%